Synchronous Juvenile ossifying Fibroma in maxilla and mandible- A case report - Shrestha, B; Subedi, S; Pandey, S (Journal of Chitwan Medical College, 2014)
Juvenile ossifying fibroma (JOF), one of the fibroosseous lesions is an uncommon clinical entity and involving both jaw is even rarer. Here, we present the case of a 15-year-old female patient with synchronous occurrence of JOF in the right sided maxilla and in the periapical area of mandibular right premolar molar region. After the clinical, radiographical and histopathological examination, the surgical treatment was carried out and the patient was kept under long term follow up. Owning to its aggressive local behaviour and high recurrence, early diagnosis, appropriate treatment and long term regular follow up are of prime importance. DOI: http://dx.doi.org/10.3126/jcmc.v4i2.10867 Journal of Chitwan Medical College 2014; 4(2): 54-57